Combining SERS and microspectrofluorimetry with historically accurate reconstructions for the characterization of lac dye paints in medieval manuscript illuminations1. (18th November 2014) - Castro, Rita; Pozzi, Federica; Leona, Marco; Melo, Maria João; Ropret, Polonca; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> In the present study, a number of dark red microsamples from nine illuminated manuscripts of three important medieval Portuguese monasteries (St. Mamede of Lorvão, Holy Cross of Coimbra and St. Mary of Alcobaça) were analyzed using a multi‐analytical approach to identify the dyes, fillers, binders and other additional paint components. Historically accurate reconstructions of lac dye paints were prepared according to recipes from medieval treatises and characterized as reference materials. Its purpose was to create better means to study this complex dye, by using the materials and techniques as close as possible to the medieval ones and ultimately build a solid database to support the interpretation of the results obtained from the spectroscopic techniques. Surface‐enhanced Raman spectroscopy (SERS) and microspectrofluorimetry were used here for the first time as complementary techniques to characterize lac dye paints, whereas Raman microscopy and micro‐Fourier transform infrared spectroscopy were employed to detect binders and fillers. While SERS was able to offer a conclusive molecular fingerprint of lac dye, microspectrofluorimetry provided useful information on the global formulation of the red paints. Copyright © 2014 John Wiley & Sons, Ltd.